The Development of a New Design Procedure for Conventional Single-Plate Shear Connections - Muir, Larry S.; Thornton, William A. (Engineering Journal, 2011)
Conventional single-plate shear connections are common and economical connections. The design procedure outlined in the 13th edition AISC Steel Construction, (AISC, 2005a), Manual relies on the bolt shear values given in the 2005 AISC Specification for Structural Steel Buildings (AISC, 2005b). The nominal bolt shear values listed in Specification Table J3.2 have historically been 20% lower than the theoretical bolt values. This reduction was provided to account for uneven force distribution among the bolts in end-loaded connections, such as bolted lap splices. The reduction served the secondary function of providing an additional factor of safety for all bolted connections designed in accordance with the Specification. The design procedure for conventional single-plate shear connections contained in the 13th edition Manual relied on this reduction to justify the practice of neglecting eccentricity in the bolt group for most configurations. The 2010 AISC Specification increases the nominal bolt shear values, necessitating a revised design procedure for single-plate shear connections in the 14th edition AISC Manual. This paper outlines the revised procedure.